Na冷却高速炉におけるNa中での水素の存在形態に着目した挙動推定 - 下山, 一仁; 加藤, 篤志; 宮本, 明; 山本, 智彦; 畠山, 望; 荒, 邦章; 三浦, 隆治; 宮本, 直人 (Journal of Computer Chemistry, Japan, 2022)
In the cooling system of sodium-cooled fast reactors, it is required to identify and rapidly detect hydrogen explosively produced by the sodium-water reaction when a water leak occurs due to damage of a heat exchanger tube in a steam generator (SG), in contrast to low-concentration background hydrogen permeating through SG tubes during normal operation. In the present study, we focus on the difference between the background hydrogen and the hydrogen generated by the sodium-water reaction, and theoretically estimate the hydrogen behavior in liquid sodium by using computational chemistry methods. We find that dissolved H or NaH, rather than H2, is the predominant form of the background hydrogen in liquid sodium, and that hydrogen produced in large amounts by the sodium-water reaction can exist stably as fine bubbles with a NaH layer on their surface.